2014
DOI: 10.1111/sms.12282
|View full text |Cite
|
Sign up to set email alerts
|

Single‐leg drop landing motor control strategies following acute ankle sprain injury

Abstract: No research currently exists investigating the effect of acute injury on single-limb landing strategies. The aim of the current study was to analyse the coordination strategies of participants in the acute phase of lateral ankle sprain (LAS) injury. Thirty-seven participants with acute, first-time, LAS and nineteen uninjured participants completed a single-leg drop landing task (DL) on both limbs. 3-dimensional kinematic (angular displacement) and sagittal plane kinetic (moment of force) data were acquired for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
54
6
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 36 publications
3
54
6
1
Order By: Relevance
“…The biomechanics literature is replete with a large quantity of investigations, which have performed laboratory analyses of dynamic movement tasks in cohorts with musculo‐skeletal impairment. For example, researchers have sought to evaluate the movement patterns of participants with a history of lateral ankle sprain (LAS) using dynamic movement tasks across the spectrum of this injury: those who have recovered fully 1 year following their acute LAS (known as ‘copers’; Brown et al., 2008, 2009, 2012), those who are suffering the chronic sequelae associated with LAS [collectively described by the umbrella term of ‘chronic ankle instability’ (CAI)] for a minimum of 1 year following the first acute episode (Brown et al., 2006, 2008, 2010, 2011, 2012; Delahunt et al., ; Gribble & Robinson, ; Terada et al., ), and those with a current acute LAS injury (Doherty et al., 2014b, in press). There is a gap in the biomechanics literature, however, as the movement patterns, which characterize individuals after they have sustained an acute LAS injury, but have yet to develop CAI or proceed to full recovery, have not been characterized or established to date.…”
mentioning
confidence: 99%
“…The biomechanics literature is replete with a large quantity of investigations, which have performed laboratory analyses of dynamic movement tasks in cohorts with musculo‐skeletal impairment. For example, researchers have sought to evaluate the movement patterns of participants with a history of lateral ankle sprain (LAS) using dynamic movement tasks across the spectrum of this injury: those who have recovered fully 1 year following their acute LAS (known as ‘copers’; Brown et al., 2008, 2009, 2012), those who are suffering the chronic sequelae associated with LAS [collectively described by the umbrella term of ‘chronic ankle instability’ (CAI)] for a minimum of 1 year following the first acute episode (Brown et al., 2006, 2008, 2010, 2011, 2012; Delahunt et al., ; Gribble & Robinson, ; Terada et al., ), and those with a current acute LAS injury (Doherty et al., 2014b, in press). There is a gap in the biomechanics literature, however, as the movement patterns, which characterize individuals after they have sustained an acute LAS injury, but have yet to develop CAI or proceed to full recovery, have not been characterized or established to date.…”
mentioning
confidence: 99%
“…The authors believe that the 40 perturbation protocol may have elicited a fatiguing effect on the limb being tilted, that manifested itself as a distortion of the somatosensory afferents, resulting in a compromised sensorimotor system. This has been observed by Doherty et al (2015) in individuals recovering from a lateral ankle sprain. This short term reduced neuromuscular control at the ankle, specifically focal to the peroneus muscles, requires a modification of the strategy used to maintain stability, which in this case is a move away from the ankle strategy to the hip strategy; this is often seen in individuals with functional ankle instability (Pinstaar et al, 1996).…”
mentioning
confidence: 65%
“…Doherty et al (2015) observed significant increases in hip muscle activity during drop landings in participants tested within two weeks of sustaining a lateral ankle sprain compared to healthy controls. They suggested that the body unloaded the lateral ankle by exhibiting a modified centrally mediated motor response to compensate for deficits within the kinetic chain.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Previous studies have shown that individuals with FAI demonstrate altered kinematics in their functional activity. Doherty et al [26] reported that subjects in the acute phase of a lateral ankle sprain injury had a more adducted position of the ankle joint during the pre-initial ground contact of gait cycle. Subjects with FAI may also have an adducted position of the ankle joint when the ankle is in plantar flexion.…”
Section: Discussionmentioning
confidence: 99%